Cholesterol modulates type I/II TGF-β receptor complexes and alters the balance between Smad and Akt signaling in hepatocytes - Chaudhary, Roohi; Goodman, Laureen S.; Wang, Sai; Asimakopoulos, Anastasia; Weiskirchen, Ralf; Dooley, Steven; Ehrlich, Marcelo; Henis, Yoav I. (Communications biology, 2024)
Cholesterol mediates membrane compartmentalization, affecting signaling via differential distribution of receptors and signaling mediators. While excessive cholesterol and aberrant transforming growth factor-β (TGF-β) signaling characterize multiple liver diseases, their linkage to canonical vs. non-canonical TGF-β signaling remained unclear. Here, we subjected murine hepatocytes to cholesterol depletion (CD) or enrichment (CE), followed by biophysical studies on TGF-β receptor heterocomplex formation, and output to Smad2/3 vs. Akt pathways. Prior to ligand addition, raft-dependent preformed heteromeric receptor complexes were observed. Smad2/3 phosphorylation persisted following CD or CE. CD enhanced phospho-Akt (pAkt) formation by TGF-β or epidermal growth factor (EGF) at 5 min, while reducing it at later time points. Conversely, pAkt formation by TGF-β or EGF was inhibited by CE, suggesting a direct effect on the Akt pathway. The modulation of the balance between TGF-β signaling to Smad2/3 vs. pAkt (by TGF-β or EGF) has potential implications for hepatic diseases and malignancies.
Gesehen am 27.03.2024